Stability of Immobilization of Bipyridine‐proline on Zn‐Modified Bimodal Mesoporous Silicas and Recyclable Catalytic Performance in Asymmetric Aldol Reaction. Issue 11 (18th March 2019) - Zhang, Yajing; Sun, Jihong; Bai, Shiyang; Zhao, Hongwu; Wu, Xia; Panezai, Hamida
Abstract: The organic‐inorganic mesoporous materials (ZZnBMMs) were successfully synthesized by Zn‐grafting into the surface of bimodal mesoporous silicas (BMMs) via covalent bond, and then immobilization of (2 S, 2'S)‐N, N'‐([2, 2'‐bipyridine]‐3, 3'‐diyl)bis(pyrrolidine‐2‐carboxamide) (Z) onto the Zn‐modified BMMs through coordination method. The influences of washed parameters such as various solvents (petroleum ether, CH2 Cl2, CH3 OH, or DMSO) and pretreated temperature on the structural stability of obtained ZZnBMMs were investigated thoroughly, which were extensively characterized by means of XRD patterns, UV‐vis and FT‐IR spectra, N2 sorption isotherms, SEM images, and SAXS patterns. The results showed that petroleum ether could be acted as optimum solvent for washing ZZnBMMs when pre‐treated temperature was around 20 °C. The SAXS patterns evidently demonstrated that ZZnBMMs before and after washing presented the fractal features, suggesting their surface roughness and structural irregularities, in which, the mass fractal ( Dm ) values were gradually decreased along with not only the increased polarity of used solvents (petroleum ether, CH2 Cl2, CH3 OH, and DMSO), but also enhanced washing temperature of from 20–60 °C and prolonged time of from 4–168 hrs. Furthermore, the ZZnBMMs as a heterogeneous catalyst for asymmetric aldol reaction exhibited the recycled (at least 6 times) catalytic performances with high efficiency (around 92.1% yield) and good selectivity (up to 68% ee). Abstract : The heterogeneous catalyst ZZnBMMs is repeatedly used in the typical asymmetric Aldol reaction in petroleum ether washing recovery, exhibiting recycling catalytic performance (at least 6 times), high efficiency (yield of about 92.1%) and good selectivity (up to 68%).